Distinct selectivity inside self-assembled coordination cages - Liang, Yang; Zhou, Xiaojuan; Gopi, Sreeraj; Wang, Rui (Frontiers in Chemistry, 2023)
Supramolecular containers have long been applied to regulate organic reactions with distinct selectivity, owing to their diverse functions such as the ability to pose a guest molecule(s) with a certain orientation and conformation. In this review, we try to illustrate how self-assembled coordination cages could achieve this goal. Two representative cage hosts, namely, self-assembled Pd(II)-ligand octahedral coordination cages ([Pd6L4]12+) and self-assembled Ga(III)-ligand tetrahedral coordination cages ([Ga4L6]12−) are selected as the pilot hosts that this mini review covers. Representative works in this area are presented here in brief.